Structure–Function Relationships of Glycine and GABAA Receptors and Their Interplay With the Scaffolding Protein Gephyrin - Kasaragod, Vikram B.; Schindelin, Hermann (Frontiers in Molecular Neuroscience, 2018)
Glycine and gama-aminobutyric acid (GABA) are the major determinants of inhibition in the central nervous system (CNS). These neurotransmitters target glycine and GABA(A) receptors, respectively, which both belong to the Cys-loop superfamily of pentameric ligand-gated ion channels (pLICs). Interactions of the neurotransmitters with the cognate receptors result in receptor opening and a subsequent influx of chloride ions, which, in turn, leads to hyperpolarization of the membrane potential, thus counteracting excitatory stimuli. The majority of glycine receptors and a significant fraction of GABA(A) receptors (GABA(A)Rs) are recruited and anchored to the postsynaptic membrane by the central scaffolding protein gephyrin. This ~93 kDa moonlighting protein is structurally organized into an N-terminal G-domain (GephG) connected to a C-terminal E-domain (GephE) via a long unstructured linker. Both inhibitory neurotransmitter receptors interact via a short peptide motif located in the large cytoplasmic loop located in between transmembrane helices 3 and 4 (TM3-TM4) of the receptors with a universal receptor-binding epitope residing in GephE. Gephyrin engages in nearly identical interactions with the receptors at the N-terminal end of the peptide motif, and receptor-specific interaction towards the C-terminal region of the peptide. In addition to its receptor- anchoring function, gephyrin also interacts with a rather large collection of macromolecules including different cytoskeletal elements, thus acting as central scaffold at inhibitory postsynaptic specializations. Dysfunctions in receptor-mediated or gephyrin-mediated neurotransmission have been identified in various severe neurodevelopmental disorders. Although biochemical, cellular and electrophysiological studies have helped to understand the physiological and pharmacological roles of the receptors, recent atomic-resolution structures of the receptors have strengthened our understanding of the receptors and their gating mechanisms. Besides that, multiple crystal structures of GephE in complex with receptor-derived peptides have shed light into receptor clustering by gephyrin at inhibitory postsynapses. This review will highlight recent biochemical and structural insights into gephyrin and the GlyR-beta as well as GABA(A) receptors, which provide a deeper understanding of the molecular machinery mediating inhibitory neurotransmission.